LAPAROSCOPY IN GYNAECOLOGY;COMPLICATIONS & AVOIDANCE - Mohamed, Atef Wahba A.; Elsadig, Abdalla Houmode (Gezira Journal of Health Sciences, 2006)
The purpose of this paper is to carry out a systematic review of the literature regarding the complications of laparoscopic surgery in gynaecology; their incidence, causes and ways of prevention. The minimally invasive surgery has established wide acceptance by the patients because of its well recognized advantages. However, the associated complications of the surgical procedures are not perceived at the same level. The possibility of occurrence of complications with the new techniques and the new technologies are well recognized. The role of the surgeon in laparoscopic surgery is explored regarding the safety of the procedure.